2019
DOI: 10.1002/cpcb.95
|View full text |Cite
|
Sign up to set email alerts
|

A Neuron‐Glia Co‐culture System for Studying Intercellular Lipid Transport

Abstract: Neurons and glia operate in a highly coordinated fashion in the brain. Although glial cells have long been known to supply lipids to neurons via lipoprotein particles, new evidence reveals that lipid transport between neurons and glia is bidirectional. Here, we describe a co‐culture system to study transfer of lipids and lipid‐associated proteins from neurons to glia. The assay entails culturing neurons and glia on separate coverslips, pulsing the neurons with fluorescently labeled fatty acids, and then incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 12 publications
2
12
0
1
Order By: Relevance
“…Previous reports demonstrated that glial LD formation requires the fly apolipoprotein, Glaz, supporting the idea that once lipids are exported across the cell membrane of neurons, they bind to apolipoproteins in the extracellular space and are taken up by glia (Liu et al, 2017). Similar conclusions were derived from experiments with primary cultures of vertebrate neurons and glia showing a requirement for APOE for LD formation in glia (Ioannou et al, 2019b; Liu et al, 2017). In these experiments, the endocytosis inhibitor Pitstop2 completely blocked lipid transfer from neurons to glia.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Previous reports demonstrated that glial LD formation requires the fly apolipoprotein, Glaz, supporting the idea that once lipids are exported across the cell membrane of neurons, they bind to apolipoproteins in the extracellular space and are taken up by glia (Liu et al, 2017). Similar conclusions were derived from experiments with primary cultures of vertebrate neurons and glia showing a requirement for APOE for LD formation in glia (Ioannou et al, 2019b; Liu et al, 2017). In these experiments, the endocytosis inhibitor Pitstop2 completely blocked lipid transfer from neurons to glia.…”
Section: Resultssupporting
confidence: 74%
“…We used lentivirus to deliver three independent shRNAs to reduce PICALM protein compared to a non-targeting shRNA control in cultured astrocytes (Figure 5A and B). We incubated neurons with a fluorescently labelled fatty acid analog Red-C12 overnight and then co-cultured the labeled neurons with transduced astrocytes on different coverslips separated by paraffin wax (Figure 5C) (Ioannou et al, 2019b, 2019a). We found a significant reduction in the transfer of fluorescently labelled fatty acids to astrocytes when PICALM levels are reduced (Figure 5D and E).…”
Section: Resultsmentioning
confidence: 99%
“…Fragmented mitochondria are inefficient at catabolizing fatty acids and susceptible to autophagic degradation ( Rambold et al, 2015 , 2011 ). Instead, neurons transfer fatty acids to neighboring glial cells to be stored in glial lipid droplets ( Liu et al, 2015 , 2017 ; Ioannou et al, 2019a , b ; Qi et al, 2021 ). By taking up neuron-derived lipids, glia can protect neurons from lipid-mediated toxicity.…”
Section: Lipid Transport In the Nervous Systemmentioning
confidence: 99%
“…al. [8,184] demonstrated that hyperactive neurons accumulate peroxidated lipids and expel them in association with APOE-positive lipid particles. These particles are then concomitantly endocytosed by neighboring astrocytes, which incorporate the lipids as droplets.…”
Section: Astrocyte Lds In Diseasementioning
confidence: 99%